2015
DOI: 10.1101/gr.182675.114
|View full text |Cite
|
Sign up to set email alerts
|

Extensive cross-regulation of post-transcriptional regulatory networks in Drosophila

Abstract: In eukaryotic cells, RNAs exist as ribonucleoprotein particles (RNPs). Despite the importance of these complexes in many biological processes, including splicing, polyadenylation, stability, transportation, localization, and translation, their compositions are largely unknown. We affinity-purified 20 distinct RNA-binding proteins (RBPs) from cultured Drosophila melanogaster cells under native conditions and identified both the RNA and protein compositions of these RNP complexes. We identified "high occupancy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…We identified approximately 3000 individual splicing events affected by knockdown of one or more of these 56 proteins. For 12 of the RNA binding protein genes (Srp54, CG6227, Rm62, mub, qkr54B, Upf1, B52, Rbp1, elav, snRNP-U1-70K, Syp, and SC35), a separate study found a significant overlap between the regulated splicing events reported here and binding targets of the same protein using RIP-seq (Stoiber et al 2015). This suggests that the splicing events regulated by these 12 proteins are more often due to primary effects.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We identified approximately 3000 individual splicing events affected by knockdown of one or more of these 56 proteins. For 12 of the RNA binding protein genes (Srp54, CG6227, Rm62, mub, qkr54B, Upf1, B52, Rbp1, elav, snRNP-U1-70K, Syp, and SC35), a separate study found a significant overlap between the regulated splicing events reported here and binding targets of the same protein using RIP-seq (Stoiber et al 2015). This suggests that the splicing events regulated by these 12 proteins are more often due to primary effects.…”
Section: Discussionmentioning
confidence: 53%
“…This suggests that the splicing events regulated by these 12 proteins are more often due to primary effects. Stoiber et al (2015) also examined two other RNA binding proteins, TRA2 and FRM1, but they did not have a significant overlap of RIP-seq targets and regulated splicing events, suggesting indirect effects or additional nonsplicing related functions. For the remaining 42 proteins, additional studies are necessary to test whether each protein directly binds to the pre-mRNAs that are regulated to help establish primary versus secondary effects-particularly in light of the cross-regulation observed among RBPs and effects on AFE events.…”
Section: Discussionmentioning
confidence: 99%
“…Mub is a poly-C binding protein likely involved as an RNA-binding protein (Stoiber et al 2015) in posttranscriptional gene regulation, especially of splicing (Brooks et al 2015). One of its three polyC-binding, human orthologs, PCBP1, has been implicated in the translational regulation of cdc27 (Link et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a study in Saccharomyces cerevisiae estimated that an average mRNA is itself associated with ∼30 different RBPs during its lifetime (Hogan et al 2008). More recently, analyses of 20 different RBPs in Drosophila melanogaster tissue culture cells (Stoiber et al 2015) identified so-called HOT (high occupancy target) RNAs that were bound by a majority of the RBPs assayed, suggesting the existence of mRNAs whose post-transcriptional regulation is likely to be very complex. This study also revealed that the mRNAs and proteins bound to the assayed RBPs are enriched for functions in RNA metabolism, further highlighting the fact that post-transcriptional regulatory factors function together, and that their mRNAs are themselves highly regulated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in recent years have sought to gain a genome-wide view of the activity of RNPs (Tenenbaum et al 2000(Tenenbaum et al , 2002Ule et al 2003Ule et al , 2005Gerber et al 2004;Keene 2007;Hogan et al 2008;Morris et al 2010;Laver et al 2013Laver et al , 2015Chen et al 2014;Stoiber et al 2015). One powerful approach involves the identification of all of the RNA and protein components of particular RNPs by immunoprecipitation (IP) of the protein of interest followed by identification of the associated transcripts by microarray or next-generation sequencing analysis, and identification of the associated proteins by mass spectrometry.…”
Section: Introductionmentioning
confidence: 99%